2022
DOI: 10.1007/s13278-022-00902-y
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale analysis of COVID-19 tweets in the Arab region

Abstract: The COVID-19 virus has spread rapidly to the Arab World, affecting the public health and economy. As a result, people started communicating about the pandemic through social media such as Twitter. This paper utilizes text mining to extract useful insights into people's perceptions and reactions to the pandemic. First, we identified 11 general topics under which COVID-19 tweets emerging from the Arab region fall. Next, we generated training data consisting of English, multidialectal Arabic, and French tweets th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…The second limitation is that Reddit may not be considered a representative of the general public, as only a limited number of users may share their views on such a platform. However, there are already studies reported in the literature on using Reddit as a platform for public discourse and emotion analysis [36]. Further, our analysis shows that the hate groups shout the loudest and most frequently during such disease outbreaks or pandemics, which may bias the output or findings of this study.…”
Section: Limitationsmentioning
confidence: 71%
“…The second limitation is that Reddit may not be considered a representative of the general public, as only a limited number of users may share their views on such a platform. However, there are already studies reported in the literature on using Reddit as a platform for public discourse and emotion analysis [36]. Further, our analysis shows that the hate groups shout the loudest and most frequently during such disease outbreaks or pandemics, which may bias the output or findings of this study.…”
Section: Limitationsmentioning
confidence: 71%
“…These sentiment analysis studies showed that public sentiments were associated with real-time news, internet information, public health events, the number of COVID-19 cases, vaccine development, the pandemic, and announcements of political leaders or authorities [ 7 , 21 , 27 , 31 , 51 , 52 , 55 , 56 , 58 , 65 ]. Although public sentiments on COVID-19 vaccines varied significantly over time and geography [ 7 , 33 , 39 ], positive sentiments were more prevalent than negative ones regarding COVID-19 vaccines [ 7 , 19 , 20 , 22 , 25 , 29 , 33 , 41 - 44 , 46 , 47 , 51 , 57 , 60 , 62 , 65 , 70 , 72 , 76 , 78 , 84 , 85 ], with trust and anticipation being the predominant emotions [ 20 , 23 , 32 , 37 , 50 , 54 , 58 ]. However, some other studies found that negative sentiments overwhelmed positive ones, with fear being the dominant emotion [ 53 , 59 , 64 , 66 , 71 , 73 , 79 - 82 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-three studies applied social media for topic analysis on COVID-19 vaccination. Topic analysis methods included latent Dirichlet allocation (LDA) topic modeling (n=24) [ 20 , 23 , 25 , 31 , 34 , 35 , 40 , 47 , 50 , 51 , 54 - 56 , 58 , 60 , 61 , 64 , 87 - 93 ], manual coding (n=17) [ 57 , 80 , 94 - 108 ], and other algorithms (n=12) [ 26 , 43 , 62 , 109 - 117 ]. Table 2 summarizes the provaccine and antivaccine topics on COVID-19 vaccines present on social media.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations